Modeling and Simulation of Palm Oil Mill Towards Effective Supply Chain Manegement. - Fazeeda, Mohamad; Razman, Mat Tahar (2011)
This paper evaluate the current capacity of the palm oil mill. The underutilized of capacity effect of the cost of production of the mill. Data were collected from a palm oil as the case study. Modeling and simulation were used in designing and accessing the mill operation using Arena simulation. The result will help the management to do better capacity planning towards effective supply chain management.